2017
DOI: 10.2196/jmir.6957
|View full text |Cite
|
Sign up to set email alerts
|

Issues for eHealth in Psychiatry: Results of an Expert Survey

Abstract: BackgroundTechnology has changed the landscape in which psychiatry operates. Effective, evidence-based treatments for mental health care are now available at the fingertips of anyone with Internet access. However, technological solutions for mental health are not necessarily sought by consumers nor recommended by clinicians.ObjectiveThe objectives of this study are to identify and discuss the barriers to introducing eHealth technology-supported interventions within mental health.MethodsAn interactive polling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…However, telehealth has been deployed and established in other clinical contexts (eg remote mental health services), as well as in some general practices across Australia. [1][2][3][4][5][6][7][8] The Royal Flying Doctor Service operating out of its traditional bases in Queensland is one such telehealth primary care provider within this clinical context. 9 The telehealth consult shares many similar clinical elements to that of the traditional face-to-face general practice consult.…”
Section: Paul Butelmentioning
confidence: 99%
“…However, telehealth has been deployed and established in other clinical contexts (eg remote mental health services), as well as in some general practices across Australia. [1][2][3][4][5][6][7][8] The Royal Flying Doctor Service operating out of its traditional bases in Queensland is one such telehealth primary care provider within this clinical context. 9 The telehealth consult shares many similar clinical elements to that of the traditional face-to-face general practice consult.…”
Section: Paul Butelmentioning
confidence: 99%
“…These data, which are generally used for personalizing ads, were used instead to estimate a schizophrenia awareness index. Finally, Nicholas and colleagues [ 18 ] presented results from a survey completed by experts examining what they thought were the key issues with electronic health in psychiatry, including how it could be used for mental health promotion. The study identified 10 issues: access to care, integration and collaboration, education and awareness, mental health stigma, data privacy, trust, understanding and assessment of mental health, government and policy, optimal design, and engagement.…”
Section: The Special Issuementioning
confidence: 99%
“…Although DHTs hold significant promise for the improvement of various elements of behavioral health intervention, and surveys have indicated that people with SMI are enthusiastic about using technology [19,20], adoption has been slow, testing of outcomes from acceptability to effectiveness has been limited, and codified development and deployment strategies have been lacking [21][22][23][24][25][26][27][28]. These preliminary efforts need to be undertaken before their effectiveness can be tested and verified so that the resulting findings can be incorporated into the redesign and reconfiguration of DHTs to provide an optimal solution.…”
Section: The Potential Of Digital Health Tools For Psychiatric Practicementioning
confidence: 99%